What Are The Clinical And Cost-Effectiveness Differences Between Standard And Enhanced Scabies Management Protocols In Primary Healthcare Settings ? : A Systematic Review - Putu Sitha Mastika Dewi; Fenny (International Medical Journal Corp. Ltd, 2025)
Introduction: Scabies, a contagious parasitic infestation, presents a significant public health challenge globally, especially in resource-limited settings. Standard management protocols for scabies in primary care, often involving topical agents or oral ivermectin, face limitations such as reinfestation and poor adherence. Enhanced scabies management protocols, including mass drug administration (MDA) and combination therapies, have emerged to address these shortcomings. However, the comparative clinical and cost-effectiveness of these enhanced approaches versus standard protocols remain uncertain, hindering optimal decision-making. This systematic review aims to compare these aspects in primary healthcare settings. Methods: This systematic review adhered to the PRISMA 2020 guidelines. A comprehensive search was conducted across databases including PubMed, Semantic Scholar, SagePub, and Google Scholar, using PICO-based keywords. Eligibility criteria focused on comparative intervention studies (e.g., RCTs, cluster RCTs) involving human subjects with confirmed scabies, conducted in primary healthcare settings, and reporting at least one clinical outcome for active management protocols. Data on study design, participant characteristics, intervention details, primary outcomes, and economic data were extracted and synthesized. Twenty-one studies were included in the final analysis. Results: The 21 included studies comprised various designs, predominantly cluster randomized trials (n=7) and randomized controlled trials (n=9). Enhanced protocols (e.g., MDA, combination therapies) consistently demonstrated higher cure rates, often ranging from 80% to 100%, and faster symptom resolution compared to standard protocols (cure rates approximately 45% to 100%). Adverse events for both protocol types were generally mild and transient. Economic data were sparse; only two studies reported direct treatment costs for standard agents, with permethrin being more expensive than ivermectin, and sulfur often the costliest. Comprehensive cost-effectiveness analyses were largely absent, though enhanced protocols were noted to require greater upfront investment. Discussion: Enhanced scabies management protocols show superior clinical effectiveness, primarily driven by population-wide or household-level treatment strategies and combination therapies that reduce reinfestation and improve healing. While these protocols are safe, their cost-effectiveness remains largely undetermined due to limited economic data. The increased resource requirements for implementation, including training and community engagement, also pose challenges for enhanced strategies. Protocol adherence may be improved with simplified regimens in enhanced protocols. Conclusion: Enhanced scabies management protocols demonstrate superior clinical effectiveness over standard treatments in primary healthcare, particularly in high-prevalence settings, by achieving higher cure rates and faster symptom resolution with comparable safety profiles. However, their adoption is challenged by a lack of robust cost-effectiveness data and higher initial resource demands. Future research should prioritize comprehensive economic evaluations to guide policy and resource allocation for optimal scabies control.